Wireless Remote Identification and Sensing with SAW Devices - Reindl, Leonhard; Scholl, Gerd; Ostertag, Thomas; Pohl, Alfred; Weigel, Robert (IEEE 1998 MMT/AP International Workshop on Commercial Radio Sensor and Communication Techniques, 1998)
Surface acoustic wave (SAW) devices can be used as novel identification and sensor elements (transponders) that do not need any power supply and may be requested wirelessly. Such a transponder picks up an electromagnetic request signal and stores it until all echoes caused by multi-path propagation have died away. Then, a characteristic response signal is returned to the interrogator unit. Identification marks respond with their nonchanging identification pattern. In radio-link sensors, a physical or chemical quantity influences the propagation properties of the SAW and consequently changes the response pattern of the device. This paper surveys the operating principle of such sensors and their state-of-the-art performance. The discussion is illustrated by several examples such as temperature sensors and sensors for mechatronic applications.
elib2cris::1512001600,reindl1998